Should physical activity recommendation depend on state of low back pain?. (24th September 2013) - Holtermann, A.; Clausen, T.; Jørgensen, M.B.; Mork, P.J.; Andersen, L.L.
Abstract Background Leisure time physical activity is recommended for preventing long‐term sickness absence (LTSA). Although low back pain (LBP) is a risk factor for sickness absence and physical activity is recommended for people with LBP, it is unknown if leisure time physical activity prevents LTSA among persons with different levels of LBP. Methods Prospective cohort study among 8655 Danish female healthcare workers responding to a questionnaire in 2004–2005 on leisure time physical activity and LBP, and subsequently followed for 1 year on periods with LTSA ∼2 consecutive weeks or more of sickness absence in a national register of social transfer payments (DREAM). Multi‐adjusted Cox regression analysis was used to model risk estimates for LTSA associated with low, moderate, high and very high leisure time physical activity at baseline among healthcare workers with no LBP (0 days past 12 months, n = 2761), non‐chronic LBP (1–30 days the past 12 months, n = 3942) and persistent LBP (>30 days the past 12 months, n = 1952). Results A strongly reduced risk for LTSA from high leisure time physical activity was found among healthcare workers with no LBP [hazard ratio (HR): 95% confidence interval (CI) 0.47:0.23–0.97 for low vs. very high activity] and non‐chronic LBP (HR: 95%CI 0.43:0.23–0.84 of low vs. very high activity), but not among healthcare workers with persistent LBP (HR: 95%CI 1.15:0.55–2.44 of low vs. very high activity). Conclusions Leisure time physical activity is a strong predictive factor on LTSA among female healthcare workers with no and non‐chronic LBP, but not among those with more persistent LBP.